Efeitos da oclusão visual no desempenho de jovens jogadores de futebol durante a prática de jogos reduzidos - Gonçalves, Bruno (2022)
This study aimed to explore how youth players’ physical, technical and positional performance may be affected by visual occlusion during small-sided games. Under-15 players performed two experimental scenarios: a) normal situation (N), without visual occlusion; b) with visual occlusion (VO), by using an eye patch in the eye corresponding to the dominant foot. These scenarios were tested in a Gk+4vs4+Gk game format in a 50x35m pitch size. Players’ positional data was used to compute tactical and time-motion variables. In addition, technical analysis was comprised using video footage. Results reported high distance covered while walking (large effect size (ES)) under the VO condition, but also lower distances at higher speed ranges (moderate to large ES). From the technical perspective, under VO condition, players performed less successfully, and unsuccessful dribbles (both small ES) possibly as result of increased touches with non-dominant foot (small ES). In addition, lower approximate entropy values (meaning higher predictable time series) in the distance to the team (small ES) and opponent team centroid (moderate ES) were found when playing with VO. Accordingly, coaches may use the VO to expose the players to more challenging environments that guide them towards more adaptive technical actions, stable and regular movement behaviours while decreasing the physical demands.